Squeeze film characteristics of conical bearings operating with non-Newtonian lubricants – Rabinowitsch fluid model. Issue 3 (8th April 2014) - Hsu, Cheng-Hsing; Lin, Jaw-Ren; Mou, Lian-Jong; Kuo, Chia-Chuan
Abstract : Purpose: – The purpose of this paper is to present a theoretical study of non-Newtonian effects in conical squeeze-film plates that is based on the Rabinowitsch fluid model. Design/methodology/approach: – A non-linear, modified Reynolds equation accounting for the non-Newtonian properties following the cubic stress law equation is derived. Through a small perturbation method, first-order closed-form solutions are obtained. Findings: – It is found that the non-Newtonian properties of dilatant fluids increase the load capacity and lengthen the response time as compared to the case using a Newtonian lubricant; however, the non-Newtonian behaviors of pseudoplastic lubricants result in reverse influences. Originality/value: – Numerical tables for squeeze-film loads of conical plates are also provided for engineering applications.